Medication calculation skills of graduating nursing students within European context - Elonen Imane; Salminen Leena; Brasaitė-Abromė Indrė; Fuster Pilar; Kukkonen Pia; Leino-Kilpi Helena; Löyttyniemi Eliisa; Noonan Brendan; Stubner Juliane; Svavarsdóttir Margrét H.; Thorsteinsson Hrund; Koskinen Sanna (Wiley, 2022)
Aim: The aim of this study is to evaluate the medication calculation skills of graduating nursing students in six European countries and analyse the associated factors.
Background: Medication calculation skills are fundamental to medication safety, which is a substantial part of patient safety. Previous studies have raised concerns about the medication calculation skills of nurses and nursing students.
Design: As part of a broader research project, this study applies a multinational cross-sectional survey design with three populations: graduating nursing students, nurse managers and patients.
Methods: The students performed two calculations (tablet and fluid) testing medication calculation skills requiring different levels of conceptual understanding and arithmetic. The managers and patients answered one question about the students' medication kills. In total, 1,796 students, 538 managers and 1,327 patients participated the study. The data were analysed statistically. The STROBE guideline for cross-sectional studies was applied.
Results: Almost all (99%) of the students performed the tablet calculation correctly, and the majority (71%) answered the fluid calculation correctly. Older age, a previous degree in health care and satisfaction with their current degree programme was positively associated with correct fluid calculations. The patients evaluated the students' medication skills higher than the nurse managers did and the evaluations were not systematically aligned with the calculation skills tested.
Conclusions: Nursing students have the skills to perform simple medication calculations, but a significant number of students have difficulties with calculations involving multiple operations and a higher level of conceptual understanding. Due to the variation in students' medication calculation skills and the unalignment between the managers' and patients' evaluations and the calculation tests, further research is needed.
Relevance to clinical practice: Graduating nursing students enter clinical field as qualified professionals, but there is still room for improvement in their medication calculation skills. This calls for attention in the fields of clinical nursing, education and research.